The Role of Village-Owned Enterprises (BUMDES) in Community Empowerment-Based Village Development in Subur Village, Air Joman District, Asahan Regency - Angelia Mitha (Journal of Sumatera Sociological Indicators, 2023)
The existence of BUMDES aims to promote self-reliant village development and enable rural communities to compete in the external market. The purpose of this study is to investigate the development of BUMDES, its role in Subur Village's development and rural community empowerment, as well as the supporting and hindering factors of BUMDES' existence in Subur Makmur Village. The research method used a descriptive qualitative approach. The informants were the BUMDES Subur Makmur Management, BUMDES Manager, Village Head, Village Finance Officer, and Village Community. Data collection techniques included observation, interviews, literature review, and documentation. The research findings indicate that BUMDES Subur Makmur was established in 2015 and currently operates several business units such as clean water distribution and online services. BUMDES' role in physical development has a significant impact, as evidenced by the development of village wells managed by BUMDES to meet the clean water needs of the rural community. PADes funds are also allocated for the maintenance of physical facilities in the village. However, BUMDES' role in community empowerment activities has not yet been effective. This is due to the limited involvement of the community in BUMDES' business activities.